ANALYSIS OF TECHNICAL CHARACTERISTICS OF THE RADIOELECTRONIC WARFARE SYSTEMS - Yakymchuk, A.М.; Бабій, Ю.О.; Поліщук, В.В.; Селюков, О.В.; Якимчук, А.В.; Дремлюга, К.О. (Військовий інститут Київського національного університету імені Тараса Шевченка, 2024)
Given the conduct of the Joint Forces operation in eastern Ukraine and as a result of the full-scale armed aggression of the russian federation, the issue of analyzing the technical characteristics of electronic warfare equipment is relevant. At the same time, a major increase in combat capabilities in the near future will be possible due to the use of intelligent troop and weapon control systems, as well as the use of weapons that use non-traditional means of influencing the enemy. During the analysis of modern methods of electronic warfare, it was found that this industry is becoming increasingly important in the context of modern military conflicts and cybersecurity threats. The use of artificial intelligence, cyber measures and the latest technologies of electronic warfare necessitates the constant improvement and adaptation of electronic warfare strategies. Both russian and Western methods of electronic warfare are characterized by a high level of technical complexity and effectiveness. Consideration of Western approaches indicates the active role of Western countries in the development and implementation of innovative technologies for controlling and countering electronic threats. The development of electronic warfare systems is becoming more effective, fast-acting, economically profitable, and the only possible means of eliminating the technical advantage of the opposing side in the information and technological sphere. Electronic warfare is an important component of modern combat, and its importance will only grow in the future. In particular, the development of new technologies will allow the creation of more effective electronic warfare means, which will have a significant impact on the course of hostilities. Therefore, the article analyzes modern electronic warfare systems used in the Ukrainian-russian war. The main tactical and technical characteristics of these electronic warfare systems are highlighted. The issue of detecting unmanned aerial vehicles by various electronic warfare methods is also highlighted.

Враховуючи проведення операції Об’єднаних сил на сході України та внаслідок повномасштабної збройної агресії російської федерації, актуальним є питання аналізу технічних характеристик засобів радіоелектронної боротьби. Водночас основне підвищення бойових можливостей найближчим часом буде можливе за рахунок використання інтелектуальних систем управління військами та озброєнням, а також використання зброї, що використовує нетрадиційні засоби впливу на противника. У ході аналізу сучасних методів радіоелектронної боротьби виявлено, що ця галузь стає все важливішою у контексті сучасних військових конфліктів та загроз кібербезпеки. Застосування штучного інтелекту, кіберзаходів та новітніх технологій радіоелектронної боротьби зумовлює необхідність постійного вдосконалення та адаптації стратегій електронного протистояння. Як російські, так і західні методи радіоелектронної боротьби відзначаються високим рівнем технічної складності та ефективності. Розгляд західних підходів свідчить про активну роль країн Заходу у розробці та впровадженні інноваційних технологій для контролю та протидії електронним загрозам. Розробка систем радіоелектронної боротьби стає більш ефективною, швидкодіючою, економічно вигідною, а й і єдиним можливим засобом, який нівелює технічну перевагу протилежної сторони в інформаційно-технологічній сфері. Радіоелектронна боротьба є важливою складовою сучасного бою, і її значення буде лише зростати в майбутньому. Зокрема розвиток нових технологій дозволить створювати більш ефективні засоби радіоелектронної боротьби, які матимуть значний вплив на хід бойових дій. Тому у статті проведено аналіз сучасних систем радіоелектронної боротьби, які використовуються в українсько-російській війні. Висвітлені основні тактико-технічні характеристики цих систем радіоелектронної боротьби. Також висвітлено питання виявлення безпілотних літальних апаратів різними методами радіоелектронної боротьби.
АНАЛІЗ ТЕХНІЧНИХ ХАРАКТЕРИСТИК СИСТЕМ РАДІОЕЛЕКТРОННОЇ БОРОТЬБИ
Keywords: сучасні системи радіоелектронної боротьби; військові конфлікти; електронне протистояння; інноваційні технології; протиповітряна оборона; засоби радіолокаційної розвідки; безпілотний літальний апарат; modern electronic warfare systems; military conflicts; electronic confrontation; innovative technologies; air defense; radar reconnaissance means; unmanned aerial vehicle